Boundary‐Dependent Sleep–Wake Dysregulation in Idiopathic Hypersomnia - Samantha Mombelli; Karine Lacourse; Hélène Blais; Anne‐Sophie Deshaies‐Rugama; Cynthia Thompson; Alex Desautels; Jacques Montplaisir; Milan Nigam; Christophe Moderie; Boshra Khajehpiri; Catherine Duclos; Jean Marc Lina; et al. (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Objective Idiopathic hypersomnia (IH) presents with excessive daytime sleepiness (EDS) despite apparently preserved nocturnal sleep, challenging traditional models of hypersomnolence based on sleep loss or fragmentation. We aimed to test the hypothesis that EDS in IH reflects excessive stabilization of the sleep state, consistent with dysfunctional thalamocortical control rather than impaired sleep quantity or continuity. Methods We analyzed overnight polysomnography from 62 IH and 81 age‐ and sex‐matched healthy controls using sleep bout duration, sleep stage transition dynamics, and automated spindle detection. Principal component analyses derived composite indices of NREM and REM sleep stability. Group differences were assessed using ANCOVAs controlling for age and sex, and associations with EDS severity were examined. Results Compared with controls, IH patients showed reduced transitions from N3 sleep toward lighter stages and wakefulness. Moreover, REM sleep was characterized by longer durations, fewer transitions to wakefulness, and more frequent transitions to lighter stages. In parallel, spindle amplitude was reduced in IH while spindle density was preserved, and smaller spindle amplitudes were associated with shorter latencies on the Multiple Sleep Latency Test. Interpretation IH is characterized by excessive N3 stabilization and reduction in transitions toward wakefulness in both NREM and REM sleep. These findings suggest that altered sleep–wake dynamics, rather than impaired sleep continuity, may contribute to persistent daytime sleepiness in IH and support sleep stability as a potential target for future research and therapeutic strategies.